The prognostic analysis of further axillary dissection in breast cancer with 1-2 positive sentinel lymph nodes undergoing mastectomy - Zhao, Xueyi; Yang, Liu; Cao, Congbo; Song, Zhenchuan (Frontiers in Oncology, 2024)
Background The ACOSOG Z0011 study has shown that axillary lymph node dissection (ALND) is an option to be considered in patients who had 1-2 metastatic sentinel lymph nodes (SLNs) who proceed with breast-conserving along with postoperative radiotherapy. However, there remains controversy regarding the applicability of this approach in patients who had a mastectomy. The aim of our study is to determine the prognostic differences and risk factors associated with the decision to opt for ALND in breast cancer patients who had 1-2 metastatic SLNs who receive a mastectomy. Methods The study conducted a retrospective analysis of patients diagnosed with cT1-2N0 breast cancer and treated at The Fourth Hospital of Hebei Medical University between January 2016 and December 2021, and patients were divided into two cohorts according to whether ALND was performed after sentinel lymph node biopsy (SLNB): SLNB cohort and SLNB + ALND cohort. Outcomes included the locoregional recurrence rate (LRR), disease-free survival (DFS), and overall survival (OS). Propensity score matching (PSM) was conducted to ensure the balance of variables between the two cohorts. Cox proportional hazard models were employed to ascertain the univariate and multivariate relative risks associated with survival. Results There were 812 cases enrolled. After the PSM, 234 receiving ALND and 234 not receiving ALND were matched. A median follow-up period of 56.72 ± 20.29 months was observed. During that time, no significant difference was identified in the DFS and OS in the SLNB + ALND cohort and the SLNB cohort (P = 0.208 and P = 0.102), except for those under 40 years old, SLNB + ALND group showed a reduction in LRR compared to SLNB group (11.1% vs. 2.12%, P = 0.044). Multivariate Cox analysis showed that younger (≤ 40 years), progesterone receptor (PR)-negative, and SLNB alone were independent risk factors for LRR; perineural invasion was a risk factor, while endocrinotherapy was a beneficial prognostic indicator for DFS and OS among patients with positive hormone receptor. Conclusion ALND does not impact DFS and OS in patients with 1-2 metastatic SLNs who have completed a mastectomy. Being younger (≤ 40 years), having a negative PR, and undergoing SLNB alone were independent risk factors for LRR. Given this finding, we recommend avoiding axillary treatment such as ALND or radiotherapy in patients without risk factors.